Highly efficient film-like nanocellulose-based adsorbents for the removal of loose reactive dye during textile laundering. Issue 6 (March 2019) - Vivod, Vera; Neral, Branko; Mihelič, Aleš; Kokol, Vanja
Cellulose nanofibrils (CNFs) were surface functionalized with hexamethylenediamine (HMDA) and, further, integrated with native CNFs in various weight mass ratios to fabricate water-stable films by the solvent casting method, to be used for the removal of tri-chromatic and anionic black reactive dye with the highest bleeding effect in the very first minutes of textile laundering, and in a weight mass compared to a commercial color-catcher sheet (Delta Pronatura (DP)). The effects of CNF-HMDA content on film bath absorption, surface potential and contact angle properties, as well as dye removal kinetics from different laundering baths (A – without and B – with a detergent) in up to 140 min were studied at 20℃ versus 60℃ and using different dye concentrations (0.1–1 g/L). It was found that bath absorption is decreased significantly (up to 60%) by increasing the CNF-HMDA content in the films, as compared to using a DP color-catcher sheet, due to a morphologically denser structure with surface-positioned hydrophobic ethylene moieties of HMDA, as well as reducing electrostatic attraction groups of CNF and HMDA. Such a surface interacts kinetically faster with anionic and hydrophobic dye molecules already at 20℃, reaching up to 37–80% removal of all dye colorants in the first 20 min. In contrast, the dye removal efficacy of the DP color-catcher sheet is due to it interacting with a cationic polymer being released from the surface, which is better only for a bluish color, and at 60℃, while being between 30% and 48%, as its release is hindered and reduced by the deposition of surfactants from the detergent.